Respuesta :
y = -3x+8
y = -5x-2
------------
y = 5(-3x+8)
y = 3(-5x-2)
---------------
y = -15x+40
y = -15x-6
--------------
y = -15x+40
- -
y = -15x-6
--------------
y = 46
y = -3x+8
46 = -3x+8
-8 -8
---------------
38 = -3x
---- ----
-3 -3
12.666...=x
(12.666.,46) ← Answer
y = -5x-2
------------
y = 5(-3x+8)
y = 3(-5x-2)
---------------
y = -15x+40
y = -15x-6
--------------
y = -15x+40
- -
y = -15x-6
--------------
y = 46
y = -3x+8
46 = -3x+8
-8 -8
---------------
38 = -3x
---- ----
-3 -3
12.666...=x
(12.666.,46) ← Answer
remember you can do anything to an equation as long as you do it to both sides
notice that they both equatl y
therefor they are equal
-3x+8=y=-5x-2
-3x+8=-5x-2
add 5x to both sides
2x+8=-2
minus 8 from both sides
2x=-10
divide by 2
x=-5
plug in -5 for x in any equation to evaluate y
y=-3x+8
y=-3(-5)+8
y=15+8
y=23
the solution is
x=-5
y=23
(-5,23)
notice that they both equatl y
therefor they are equal
-3x+8=y=-5x-2
-3x+8=-5x-2
add 5x to both sides
2x+8=-2
minus 8 from both sides
2x=-10
divide by 2
x=-5
plug in -5 for x in any equation to evaluate y
y=-3x+8
y=-3(-5)+8
y=15+8
y=23
the solution is
x=-5
y=23
(-5,23)